Tu ran wang ming tian ya = Lie down with lions - Follett, Ken, 1949-; Liu, Yang (Nanjing : Jiang su feng huang wen yi chu ban she, 2017)
This book is a modern British novel. Tells: Jane accidentally discovered that he was deceived by his beloved boyfriend Ellis. After being hit hard, she married the pursuer Jean-Pierre, who went to Afghanistan and became a local medical worker. I thought that I started a new life, but found myself in a greater betrayal and conspiracy... At this time, Ellis also came to Afghanistan. Love, lies, war, hatred, the fate of the three people was pushed further and further, and eventually led to a nightmare-like life and death.
062 Flett Classics Suspense Novels
Keywords: English fiction -- Translation into Chinese; Chinese fiction -- Translation from English; Suspense fiction